The use of passive structures in ESL narrative compositions among Malay students / Junisah Mohd Fadzli Kalimuttu - Junisah, Mohd Fadzli Kalimuttu (2016)
Narrative compositions provide essential information regarding writers‟ linguistic competence. This study was conducted to explore the use of passive structures in English as a Second Language (ESL) narrative compositions, and specifically, to describe the passive voice structured by Malay students and the effect of their mother tongue (the Malay language) in constructing the passive structures in English. The study combined both the quantitative and qualitative methods, using the Lexical Functional Grammar (LFG) by Joan Bresnan as the theoretical framework of the study because it involves both the constituent (c-structure) and the functional structure (f-structure) in sentence analysis. Therefore, a better illustration and explanation on the function-dependent rules like passivisation across languages are better portrayed. This study involved thirty Form 4 Malay students of intermediate level of proficiency, from SMK Tanjung Datuk, Pengerang Johor, Malaysia. The participants were given a question on a narrative composition taken from the 2014 SPM 1119/1 English Paper to be answered within one hour. Interviews with three participants were also conducted to further clarify the data gathered. The findings showed that the structures of the passive voice in the ESL narrative compositions of the Malay participants comprised adjectival, resultative and verbal passives. The participants were able to utilize the passive voice in their ESL narrative compositions, but the structures written were mostly inaccurate due to the influence of their mother tongue (the Malay language) particularly on sentence types, sentence patterns and the formation of the passive verbs. The study is significant to the field of language learning and assessment as it can fill the gap to the current knowledge of the use of passives among Malay secondary school students in their narrative compositions and it reveals the root of the difficulties that the English as a second language (ESL) Malay students are facing when using the passive voice in their v narrative writing, thus aiding teachers to come up with solutions to tackle the problem.